GAMBARAN HITUNG JUMLAH LEUKOSIT ANTARA LARUTAN TURK DAN LARUTAN TURK MODIFIKASI DENGAN PENAMBAHAN AIR PERASAN JERUK NIPIS DAN SARI UMBI BIT - hamril dani; Sri Hartini Harianja; Mardyana Nizar; Tarisa Suma Lestari (Journal of Medical Laboratory and Science, 2024)
Hematological examination that is often done is counting the number of leukocytes, which is carried out using turk's solution. The high number of inspections causes more waste. To anticipate this condition, research is conducted to find an alternative to Turk's solution. The purpose of this study was to determine the difference in the number of leukocytes between the turk solution and the modified turk solution by adding lime juice and beetroot juice. This type of research is observational. The research population is the TLM Department of Health Poltekkes, Palembang in 2021 with sample of 10 students. The sampling technique used is purposive sampling. The leukocyte count was done manually. The results were analyzed by T-independent test. The results of the number of leukocytes with turk's solution an average of 7.215, the number of leukocytes with modified turk's solution an average of 6.140 with a P-value of 0.920. The conclusion is there is no significant difference in the number of leukocytes between the turk solution and the modified turk solution by adding lime juice and beetroot juice, lime juice at concentration of 2% is best at lysing erythrocytes, beetroot juice at concentration of 1% is best at giving color to leukocytes.